The Human Microbiome, an Emerging Key-Player in the Sex Gap in Respiratory Diseases - Beauruelle, Clémence; Guilloux, Charles-Antoine; Lamoureux, Claudie; Héry-Arnaud, Geneviève (Frontiers in Medicine, 2021)
The sex gap is well-documented in respiratory diseases such as cystic fibrosis and chronic obstructive pulmonary disease. While the differences between males and females in prevalence, severity and prognosis are well-established, the pathophysiology of the sex difference has been poorly characterized to date. Over the past 10 years, metagenomics-based studies have revealed the presence of a resident microbiome in the respiratory tract and its central role in respiratory disease. The lung microbiome is associated with host immune response and health outcomes in both animal models and patient cohorts. The study of the lung microbiome is therefore an interesting new avenue to explore in order to understand the sex gap observed in respiratory diseases. Another important parameter to consider is the gut-lung axis, since the gut microbiome plays a crucial role in distant immune modulation in respiratory diseases, and an intestinal “microgenderome” has been reported: i.e., sexual dimorphism in the gut microbiome. The microgenderome provides new pathophysiological clues, as it defines the interactions between microbiome, sex hormones, immunity and disease susceptibility. As research on the microbiome is increasing in volume and scope, the objective of this review was to describe the state-of-the-art on the sex gap in respiratory medicine (acute pulmonary infection and chronic lung disease) in the light of the microbiome, including evidence of local (lung) or distant (gut) contributions to the pathophysiology of these diseases.